Strategies used by nurses regarding underreporting of rural work accidents due to pesticide use - Dionatan Carmini de Brito; Daiani Modernel Xavier; Alberto de Oliveira Redü; Luciano Garcia Lourenção; Franciele Gomes Soares; Giovana Calcagno Gomes; Laura Fontoura Perin (Associação Brasileira de Enfermagem, 2024)
ABSTRACT Objective: To learn the strategies used regarding underreporting of pesticide use in rural areas. Methods: A qualitative study was carried out in eight primary healthcare units in rural areas and two emergency care units in a municipality in southern Brazil. Data collection took place in 2023 through interviews. Twenty professional nurses participated. The data was submitted to content analysis. Results: The strategies identified were lifelong and continuing education for the professionals who carry out the notification, active search and training of workers who deal directly with this type of substance, computerizing the notification by filling in the forms online, and carrying out research on the subject. Final considerations: Nurses play an important role in reporting occupational accidents caused by the use of pesticides, improving occupational safety in rural areas.